1981
DOI: 10.1192/bjp.138.2.110
|View full text |Cite
|
Sign up to set email alerts
|

School Phobia: A Therapeutic Trial with Clomipramine and Short-Term Outcome

Abstract: SummaryA double-blind trial failed to demonstrate any significant short-term effects of clomipramine in doses recommended for use in general practice (in addition to the usual range of psychotherapeutic help) in the treatment of children with school refusal and neurotic disorder. Patterns of improvement were also studied for the sample as a whole irrespective of treatment. Neither age nor sex were significantly related to improvement, except on one behavioural measure where girls initially did better than boys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(58 citation statements)
references
References 21 publications
0
55
0
3
Order By: Relevance
“…Results have been mixed, with some studies showing superiority to placebo (12,13) and others not (14)(15)(16). Owing to their risk of cardiac toxicity and potential anticholinergic side effects, tricyclics have recently fallen out of favour in the treatment of childhood anxiety disorders.…”
Section: Psychotropic Medication In Childhood Anxiety Disordersmentioning
confidence: 99%
“…Results have been mixed, with some studies showing superiority to placebo (12,13) and others not (14)(15)(16). Owing to their risk of cardiac toxicity and potential anticholinergic side effects, tricyclics have recently fallen out of favour in the treatment of childhood anxiety disorders.…”
Section: Psychotropic Medication In Childhood Anxiety Disordersmentioning
confidence: 99%
“…Eight of the 14 studies were federally funded, 4 were industry funded, and funding data were unavailable for 2 of these studies (Simeon et al 1992;Berney 1981). The average number of sites per trial was 14 -20 and five trials (36%) were single-site studies.…”
Section: Characteristics Of Participants and Studies Includedmentioning
confidence: 99%
“…The only placebo-controlled clinical trial to evaluate clomipramine in children and adolescents with school refusal also showed similarity between its clinical response and the one observed with placebo (Berney et al 1981). In this study, subjects may have taken subdoses, as only low doses of clomipramine (40-75 mg/day) were used.…”
mentioning
confidence: 64%
“…The only (double-blind) treatment trial, with children with school refusal and neurotic disorder, failed to demonstrate any significant short-term effects of clomipramine. It is noteworthy, however, that subjects in this study had heterogeneous diagnoses and were submitted to small dose regimens (40-75 mg/ day) (Berney et al 1981). In contrast with the scarcity of studies with clomipramine in GAD, SAD, and SP, children and adolescents with another AD, obsessive-compulsive disorder (OCD), have long been successfully treated with this compound (Leonard et al 1989).…”
Section: Introductionmentioning
confidence: 99%